Hematological cancer patient‐caregiver dyadic communication: A longitudinal examination of cancer communication concordance. Issue 10 (4th August 2020) - Siminoff, Laura A.; Wilson‐Genderson, Maureen; Barta, Stefan; Thomson, Maria D.
Abstract: Objective: Informal caregivers play a fundamental role in care and decision making with hematological cancer patients. Concordant patient‐caregiver communication is a critical antecedent to high quality decision making. Little is known about patterns of dyadic communication throughout the cancer treatment continuum. The objective of this study was to assess patterns of cancer communication concordance regarding treatment and care among hematological cancer patients undergoing active treatment and their informal caregivers and test whether patterns were associated with participant characteristics. Methods: A case series of hematological cancer patient‐caregiver dyads (n = 171) were recruited from oncology clinics in Virginia and Pennsylvania and followed for 2 years. Latent Class Growth Models (LCGM) were used to analyze longitudinal data captured using Cancer Communication Assessment Tool for Patients and Families (CCAT‐PF) and the association with participant characteristics. Results: White patient‐caregiver dyads demonstrated decreased communication concordance and African American dyads demonstrated increased communication concordance over time. Lower communication concordance was found among dyads with lower levels of education and income, and cancers diagnosed at more advanced stages; these relationships were stable over time. Modeling identified the presence of three distinct communication groups (Stable Concordant (57.4%), Fluctuating Medium Concordant (37.8%), High Discordant (5.4%)) that differed by baseline level of communication concordance, patterns of concordance over time, race, income and the dyad relationship. Conclusions: Patient‐caregiver cancer communication concordance was not static overtime. Results suggest the presence of a new dyadic cancer communication typology that could help preemptively identify dyads at risk for communication difficulties that impede treatment decision making.